워드 클라우드를 활용한 심부전 환자와 의료진 간 의사소통에 대한 중요 요인 비교 - 안정아; Jeong-ah Ahn (의료커뮤니케이션, 2024)
Purpose : This qualitative study aimed to identify key factors related to effective communication, as perceived by heart failure patients and their healthcare providers. Methods : A convenience sample of 61 heart failure patients and 35 healthcare providers were recruited from a cardiovascular department at a large tertiary medical center in South Korea. Data were collected through individual interviews and analyzed using Word Cloud analysis with MAXQDA 2022 software. Results : The mean age of the patients was 65.7 years, with 66.7% male; they had been diagnosed with heart failure for an average of 6.7 years. Healthcare providers had a mean age of 34.8 years, with 68.6% female. Word Cloud analysis revealed that patients identified “Comfort” as the most critical factor for effective communication, followed by “Disease information” and “Security.” For healthcare providers, “Rapport” emerged as the most important factor, followed by “Proper explanation” and “Knowledge.” Conclusion : The study highlights both shared and distinct perspectives between heart failure patients and healthcare providers regarding the factors essential for effective communication. These findings provide valuable insights for developing targeted communication strategies that address the specific needs and perceptions of both patients and healthcare providers.